THE PROBLEM OF PERSONAL DECISION-MAKING AND SOCIAL INFLUENCE IN THE WORKS OF EASTERN PHILOSOPHERS - Xayrullayeva Zarnigor Sarvar qizi; Prof. H. Abdusamatov (Web of Journals Publishing, 2025)
This article analyzes the problem of personal decision-making and social influence in the works of Eastern philosophers. Based on the views of scholars such as Al-Farabi, Ibn Sina, Imam Ghazali, Alisher Navoi, Abu Rayhan Beruni, Yusuf Khos Khajib, Jalaluddin Rumi, Ahmad Yassavi, and Ibn Khaldun, the psychological aspects of the relationship between the individual and society are explored. The study examines the mechanisms of social influence, the characteristics of individual freedom of choice, and the interaction between the individual and society. The findings of the article have scientific and practical significance for understanding the role of social factors in the process of individual decision-making and for enriching modern psychological concepts through Eastern philosophical thought.
Keywords: Person, personal decision-making, social influence, social psychology, individual-society relations, individual freedom, social pressure, asabiyyah, masnavi.